Knowledge, Attitude and Skills of Nurses Related to the Implementation of Safewards in Mental Hospital - Tri Wahyuni; Giur Hargiana; Soimah Soimah (Indonesian Journal of Global Health Research, 2025)
Safewardis an approach to providing inpatient mental health services with the aim of minimizing the number of conflicts that arise between nurses and clients. This study aims to determine the characteristics of nurses including gender, age, education level, work experience, safewards training that has been attended and identify the description of nurse readiness including skills, perceived knowledge and attitudes. The study was conducted using a descriptive design with a sample of 124 nurses. The sample was selected using the total sampling method, namely nurses who provide direct services in the inpatient room and are willing to participate in the study. Data were collected from respondents using the primary method where respondents directly filled out the questionnaire online which was shared via google form. Univariate frequency and percentage analysis were used to analyze the collected data. The results of the study showed that 77.42% of respondents had a positive attitude towards safewards, 62.90% had good knowledge and 54.5% had high skills. The results of this study recommend the need for training on safewards at all levels of nurses to improve nurse readiness in implementing the safewards approach.